1994
DOI: 10.1111/j.1600-0560.1994.tb00688.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐selectin and vascular cell adhesion molecule‐1 as critical adhesion molecules for infiltration of T lymphocytes and eosinophils in atopic dermatitis

Abstract: To study the temporal and spatial relationship between infiltrating T-cell subsets or eosinophils and cell adhesion molecules on endothelial cells in skin lesions of atopic dermatitis (AD), we undertook immunohistochemical analysis using monoclonal antibodies against surface markers of T cells, eosinophil granule proteins and cell adhesion molecules. Predominant mononuclear cells in acute and chronic skin lesions were CD3, CD4 and CD45RO positive helper-inducer/memory T cells. Their number was significantly an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…The patients did not apply any ointment or cream on the examined sites for at least 5 days before the measurements. Concerning the inflammatory state at the clinically normal tested sites, we have previously demonstrated that clinically normal skin from patients with AD has no histologic evidence of inflammation (Wakita et al, 1994), suggesting that in the current study, no substantial inflammatory changes were present in the nonlesional skin.…”
Section: Measurement Sites Of the Skinmentioning
confidence: 77%
See 1 more Smart Citation
“…The patients did not apply any ointment or cream on the examined sites for at least 5 days before the measurements. Concerning the inflammatory state at the clinically normal tested sites, we have previously demonstrated that clinically normal skin from patients with AD has no histologic evidence of inflammation (Wakita et al, 1994), suggesting that in the current study, no substantial inflammatory changes were present in the nonlesional skin.…”
Section: Measurement Sites Of the Skinmentioning
confidence: 77%
“…Since clinically normal skin in patients with AD has minimal or no inflammation (Wakita et al, 1994), this observation strongly suggests that defects in the permeability barrier function in AD are intrinsic and are not associated with inflammatory events. Although there was a significant increase both in PA signals and in TEWL values in AD compared with healthy controls, the degree of barrier disruption in AD expressed as a relative ratio to healthy controls was greater with the PAS method (2.98-to 1.8-fold) than with the TEWL measurement (1.73-fold).…”
Section: Hata Et Almentioning
confidence: 86%
“…Collectively, our fi ndings suggest that cutaneous infl ammatory reaction induced by a variety of environmental irritants and allergens or scratching may trigger the expression of susceptibility gene, probably including sphingomyeline/glucosylceramide deacylase enzyme, resulting in the ceramide defi ciency which in turn leads to the barrier disruption in the AD skin. It seems reasonable to assume that once-expressed susceptibility gene never disappears for a long period of time, even after infl ammation is attenuated, in turn leading to the continued barrier disruption even in the nonlesional skin without any infl ammation [30] .…”
Section: Discussionmentioning
confidence: 99%
“…In the chronic skin lesions of AD, cells containing IFN-␥ mRNA and protein predominate over those containing IL-4 and IL-5 (3). Vascular endothelial cells in AD skin lesions have increased expression of the adhesion molecules E-selectin, VCAM-1, and ICAM-1 (4,5). Products of eosinophils, which express VLA-4, the counterligand for VCAM-1, are readily detectable in the skin lesions of AD (6).…”
Section: Introductionmentioning
confidence: 99%